THE APPLICATION OF STAD TO TEACH WRITING NARRATIVE TEXT TO THE FIRST GRADE OF SMAN 10 SURABAYA (RETAIN, 2014)
Penelitian ini dibuat untuk menggambarkan penerapan tekhnik Student Team Achivement Division (STAD) untuk mengajar menulis teks naratif untuk kelas 1 Sekolah Menengah Atas. Penelitian ini mengambil beberapa permasalahan: (1) bagaimana penerapan tekhnik STAD dalam mengajar menulis teks naratif untuk kelas 1 SMA? (2) bagaimana hasil menulis teks naratif siswa setelah diterapkan tekhnik STAD? Dan (3) bagaimana tanggapan siswa terhadap tekhnik STAD dalam pembelajaran menulis teks naratif? Ketika tekhnik STAD diterapkan dalam kelas Bahasa Inggris hususnya pelajaran menulis teks naratif. Hal ini bisa dijelaskan bahwa tekhnik ini bisa diterapkan di kelas Bahasa Inggris dan siswa tertarik dengan tekhnik ini. Hal ini bisa dilihat dari hasil quisioner; 12% dari mereka memilih sangat menarik. 68%, memilih menarik, 16% memilih kurang menarik dan hanya 6% memilih tidak menarik. Penelitian ini membuktikan bahwa tekhnik STAD dapat membantu siswa dalam membuat tulisan teks naratif. Penelitian ini menunjukkan manfaat dari tekhnik STAD terhadap hasil tulisan siswa. Berdasarkan tulisan siswa menunjukkan hasil yang baik setelah dianalisis dengan menggunakan penilaian ESL oleh Jacob. Analisis hasil meliputi isi tulisan, kosa kata, organisasi, bahasa yang digunakan, dan mekanik. Komposisi penilaiannya berdasarkan empat tingkatan, yaitu; sempurna, sangat baik, baik – lumayan, lumayan – jelek, dan sangat jelek. Kata kunci: menulis, teks naratif dan STAD. Abstract This study is designed to describe the application of Student Team Achievement Division (STAD) technique in teaching narrative writing to the fisrt grade of senior high school. This study composes some questions: (1) How is the application of Student Team Achievement Division (STAD) in teaching writing narrative text to the first grade of senior high school? (2) how is the writing of the students after they studied by using STAD technique? And (3) how are the students’ responses toward the teaching and learning process of writing narrative text through STAD technique? Since the STAD Technique was applied in English class especially in learning writing narrative text, it can be explained that this technique is applicable and students were interested in it. It can be seen by the students' response that 12 % of the students said that it was very interesting, 68% said it was interesting, 16 % said it was less interesting and only 6 % said it was not interesting. This study has proved that the STAD Technique can help the students in composing writing a narrative text. The study shows the benefits of the STAD Technique towards the students writing composition. The students’ composition showed good result after being analyzed by using ESL Composition Measurement by Jacob. The analyzing was including content, organization, vocabulary, language used, and mechanics. The composition was scored into four levels. They are excellent to very good, good to average, fair to poor, and very poor. Key word: writing, narrative text and STAD.